Forests of Jammu and Kashmir - Pathania, Harnam Singh (Indian Forester, 1954)
The Department, first organised in 1891, is manned by trained foresters. Kashmir contains the finest forests under Himalayan conifers, the easier ones are managed successfully under he Uniform System and the balance under the conservative Selection. Systems Regeneration is satisfactory except of fir due to grazing, and of chir due to incendiary fires. Willow plantation has been successfully raised. Soil erosion is a problem and efforts are a foot for tackling it.The State is rich in medicinal herbs. Drug farming has recently been started. The industries, run. Successfully, are Rosin and Turpentine and Kashmir Willows. The State is rich in wildlife and is world famous for trout fishing and big game hunting.